Near-infrared light and redox dual-activatable nanosystems for synergistically cascaded cancer phototherapy with reduced skin photosensitization. (September 2022) - Li, YiCong; Hu, DanRong; Pan, Meng; Qu, Ying; Chu, BingYang; Liao, JinFeng; Zhou, XiaoHan; Liu, QingYa; Cheng, Shuang; Chen, Yu; Wei, Quan; Qian, ZhiYong
Abstract: Currently, activatable photodynamic therapy (PDT) that is precisely regulated by endogenous or exogenous stimuli to selectively produce cytotoxic reactive oxygen species at the tumor site is urgently in demand. Herein, we fabricated a dual-activatable PDT nanosystem regulated by the redox tumor microenvironment and near-infrared (NIR) light-induced photothermal therapy (PTT). In this study, photosensitizer chlorin e6 (Ce6) was conjugated to hyaluronic acid (HA) via a diselenide bond to form an amphiphilic polymer (HSeC) for loading PTT agent IR780 to produce HSeC/IR nanoparticles (NPs). The photoactivity of Ce6 for PDT was "double-locked" by the aggregation-caused quenching (ACQ) effect and the fluorescence resonance energy transfer (FRET) from Ce6 to IR780 during blood circulation. After selective accumulation into tumors, HSeC/IR NPs were subsequently dissociated due to the "double-key", which included diselenide bond dissociation under high redox conditions and IR780 degradation upon NIR laser irradiation, resulting in recovering Ce6. In vitro studies indicated that Ce6 photoactivity in HSeC/IR NPs was significantly suppressed when compared with free Ce6 or in HSeC NPs. Moreover, BALB/c mice treated with HSeC/IR NPs displayed distinctly alleviated skin damage during PDT. Synergetic cascaded PTT-PDT with superior tumor suppression was observed in SCC7 tumor-bearing mice. Therefore, the study findings could provide a promising treatment strategy for PTT-facilitated PDT with high antitumor efficacies and reduced skin phototoxicity levels.